2007
DOI: 10.1158/0008-5472.can-06-3721
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 and ErbB2 in the Cardiac Response to Doxorubicin Injury

Abstract: A major drawback to doxorubicin as a cancer-treating drug is cardiac toxicity. To understand the mechanism of doxorubicin cardiac toxicity and the potent synergic effect seen when doxorubicin is combined with anti-ErbB2 (trastuzumab), we developed an in vivo rat model that exhibits progressive dose-dependent cardiac damage and loss of cardiac function after doxorubicin treatment. The hearts of these animals respond to doxorubicin damage by increasing levels of ErbB2 and the ErbB family ligand, neuregulin 1B, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…Clinical studies using radiolabeled anti-ErbB2 and SPECT imaging showed that more anti-ErbB2 binds in the heart after doxorubicin treatment (3). These clinical studies are in agreement with our earlier findings that doxorubicin increases ErbB2 in the rat heart (19). In the current study, our findings that GPx and catalase activities are elevated additionally support the antioxidant role of ErbB2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Clinical studies using radiolabeled anti-ErbB2 and SPECT imaging showed that more anti-ErbB2 binds in the heart after doxorubicin treatment (3). These clinical studies are in agreement with our earlier findings that doxorubicin increases ErbB2 in the rat heart (19). In the current study, our findings that GPx and catalase activities are elevated additionally support the antioxidant role of ErbB2.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical link between ErbB2 and heart function was discovered when 27% of ErbB2-overexpressing breast cancer patients treated with doxorubicin and anti-ErbB2 (Trastuzumab/Herceptin) subsequently developed a synergistic cardiac toxicity (57,65). We previously reported that doxorubicin treatment induces the expression of ErbB2 in rat heart (19), but it is still unknown whether this ErbB2 upregulation might serve to counteract oxidative stress induced by doxorubicin. If so, an upregulation of ErbB2 protein in cardiomyocytes could represent a molecular target for anti-ErbB2 therapy to reverse any cardioprotective mechanisms attributed by ErbB2.…”
Section: This Is the First Study On Erbb2 Overexpression In The Heartmentioning
confidence: 99%
“…In agreement with previous studies and in line with the findings derived from human studies, doxorubicin in our model led to severely reduced LV systolic and diastolic function, which consequently resulted to decreased global heart function as indexed by suppressed CO (8,20). The inhibition of HMG-CoAreductase by pretreatment with fluvastatin improved LV function under these conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Images are representative from three different cell preparations. Scale bar corresponds to 10 μm vitro studies using primary cardiomyocytes (Gabrielson et al 2007;Solem et al 1996;Zhou et al 2001) or other cell lines (L'Ecuyer et al 2001;Spallarossa et al 2004) have been widely reported in the literature. From the different models used, some conclusions are common to all: (a) Dox is activated at the mitochondrial level, forming a semiquinone radical, and (b) Dox causes oxidative stress in cardiac cells that particularly affects mitochondria (Berthiaume and Wallace 2007;Wallace 2003).…”
Section: Discussionmentioning
confidence: 99%